Tax audits and their effects on tax compliance - Sebastian Beer; Brian Erard; Matthias Kasper; Erich Kirchler (EconPol Forum, 2025)
Tax administrations increasingly use audits via mail (correspondence audits) to audit taxpayers. Correspondence audits are cheaper than face-to-face audits but their effects on compliance are unclear. We investigate the effects of correspondence and face-to-face audits on post-audit tax reporting. We find that face-to-face audits generally have strong positive effects on subsequent compliance. Correspondence audits sometimes reduce compliance, impacting the optimal balance between audit types.
Keywords: 330